73 A positive experience in the use of a private messaging service (whatsapp) for inpatient care. (31st October 2017) - Abdulla, Muaad
Abstract : The traditional way of communicating in acute hospitals involves using a pager system. Followed by an inevitable phone call to one individual. This can sometimes make reaching the right clinical staff member a cumbersome task when jobs are delegated throughout the day. By encouraging the use of the private messaging service 'Whats app' in the gastroenterology department we have found that our communication has become more efficient. In addition, there is less duplication of jobs and quicker responses to urgent tasks. Communicating in a 'group chat' can allow contact with the whole medical team leading to a more well-organised work force. This can potentially contribute to a reduction in human error as there would be an electronic record of tasks and requests which can be reviewed. Inherent to Whats app is end to end encryption which can prevent the risk of patient information being accessed illegally. Furthermore, if used with safeguards to protect patient confidentiality then the use of this app can be a safe as well as innovative way of enhancing the working environment in the NHS.